Drug utilization patterns of antibiotics in outpatient department of educare dental hospital at Malappuram, Kerala, India - K., Fayisa; P., Anas P.; A., Sudhakar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug utilization studies aims to evaluate factors related to the prescribing, dispensing, administering and taking of medication, and its associated events. Antibiotic prescription by dental practitioners has an important impact on the rate of general antibiotic prescription use, and an attempt has been made to establish a surveillance system for the monitoring and control of the use of these drugs. Methods: Retrospective record-based study was conducted at outpatient department at Educare Dental College and Hospital, Chattipparamba, Malappuram, Kerala. About 2802 prescriptions were screened, drugs prescribed were noted, tabulated and analysed. Results: Total no. of prescriptions 2802, total no. of antibiotics prescribed 2916, average no of antibiotics per prescription 1.04. Out of antibiotics prescribed 72% were monotherapy and 28% were fixed dose combination. Among antibiotics beta lactam antibiotics were commonly prescribed followed by nitroimidazoles and macrolides. Conclusions: The study was conducted to analyze the drug utilization pattern in outpatient department at dental hospital. Most of prescription were rational, both monotherapy and polypharmacy were practiced. Safer drug with less adverse effect profile were considered. Among the antibiotic amoxicillin was the commonest.